A conceptual automated negotiation model for decision making in the construction domain - Mahmoud M.A.; Ahmad M.S.; Yusoff M.Z.M. (Springer Verlag, 2023)
Artificial intelligence; Automation; Autonomous agents; Decision making; Distributed computer systems; Intelligent agents; Multi agent systems; Network architecture; Automated negotiations; Conflict resolution algorithms; Decision making process; Intelligent software agent; Multiagent negotiation; Negotiation algorithm; Negotiation protocol; Value management; Software agents